Searching for a Smart City: A Bibliographic Analysis of 'Public Facing' EU Smart City Projects. (7th May 2021) - Collins, Alan; Cox, Adam; Torrisi, Gianpiero
Abstract: The narrative used to describe smart cities, including the experimentation on them, affects the perception of the smart city. This study systematically assembles and analyses 'public facing' smart city project data from across the EU. Using a bibliographic analysis, including word frequency analyses across time and countries of project descriptions, we identify the dominant themes and constructs in the smart city narratives used by teams advancing smart city projects. The study highlights spatial and intertemporal variations in locational density, differing project content and the range of conceptual emphases. Results show that the main concern of smart city narratives in the EU is firmly centred on energy. We argue that policy‐makers should aim for better alignment of smart cities' narrative with citizens' perception or, at least, a wider description of the very nature of implemented projects to include those rather neglected aspects might attract more interest and citizens' involvement.